2018
DOI: 10.1126/scisignal.aaj1757
|View full text |Cite
|
Sign up to set email alerts
|

The Hippo pathway effector TAZ induces TEAD-dependent liver inflammation and tumors

Abstract: The Hippo signaling pathway regulates organ size and plays critical roles in maintaining tissue growth, homeostasis, and regeneration. Dysregulated in a wide spectrum of cancers, in mammals, this pathway is regulated by two key effectors, YAP and TAZ, that may functionally overlap. We found that TAZ promoted liver inflammation and tumor development. The expression of TAZ, but not YAP, in human liver tumors positively correlated with the expression of proinflammatory cytokines. Hyperactivated TAZ induced substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 38 publications
(48 reference statements)
0
56
0
1
Order By: Relevance
“…Moreover, using the microRNA.org database to analyze miR‐223 targeted genes among these up‐regulated genes, we identified seven potential targets of miR‐223 that are related to liver carcinogenesis, including Cxcl10 , Taz , Serpinb9 , Nrxn1 , Slc1a4 , Slc16a6 , and Dock11 . Among these genes, Taz is a well‐documented oncogenic gene that encodes a protein to promote liver cancer development . Therefore, miR‐223 can directly target multiple oncogenic genes including Taz , thereby attenuating NASH‐associated HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, using the microRNA.org database to analyze miR‐223 targeted genes among these up‐regulated genes, we identified seven potential targets of miR‐223 that are related to liver carcinogenesis, including Cxcl10 , Taz , Serpinb9 , Nrxn1 , Slc1a4 , Slc16a6 , and Dock11 . Among these genes, Taz is a well‐documented oncogenic gene that encodes a protein to promote liver cancer development . Therefore, miR‐223 can directly target multiple oncogenic genes including Taz , thereby attenuating NASH‐associated HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The oncogenic role of nuclear YAP1 may also be linked to mechanical damage secondary to the accumulation of bile acids which activate YAP1 via a pathway dependent on the induction of the scaffold protein IQGAP1 [29]. On the other hand, in the liver, hyperactivated TAZ promotes inflammatory cytokine production and macrophage infiltration, playing a relevant role in tumor development [30]. Due to the relevance of inflammation in gallbladder cancer [31], we propose that nuclear translocation of YAP is a major event in the gallbladder carcinogenic process triggered by chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of TAZ, but not YAP, was found to correlate with the mRNA transcription of inflammatory cytokines CCL2 and CXCL1 in human liver tumors. Expression of TAZ in mouse livers increased the secretion of proinflammatory cytokines, recruitment of myeloid cells, and mice mortality in a TEADs dependent manner (90). Mooring et al found that the long-term expression of YAP/TAZ in hepatocyte positively correlated to the degree of liver inflammation.…”
Section: Hippo-yap and Nf-κb Signaling And Inflammationmentioning
confidence: 99%